A pragmatic analysis of positive politeness of Locked Away song lyrics by R. City feat Adam Levine - Rokhmah, Ica Khadiqotur (Maliki Interdisciplinary Journal, 2024)
This paper aims to highlight on two main objectives based on pragmatism. Firstly, to analyze the positive politeness aspect which focus on depocisy strategies used in the lyrics. Secondly, this paper also discussed about the culture relationship in term of pragmatism. Then, the data were collected by having the direct observation by analyzing the songs lyrics and library research by reading some articles which is related. The result shows that Locked Away song consist of positive politeness which consist of three main aspect discussed. These are intensify interest, seeking agreement, and including both S and H. Besides, this lyrics also introduce positive politeness in America. Thus, it has been being American culture.